Study on a New Rotor Profile with Convex Head for Radial Seal andEccentric Main Circular Arc - Li Yulong Liu Ping Zang Yong Li Xiurong Zhao Yan (Jixie chuandong, 2019)
For the need to increase effect of volume utilization rate and volume efficiency for roots pump，a new profile geometry of circular arc rotors with seal convex head and eccentric circular arc is proposed. Firstly，based on the profile geometry of common circular arc rotors，the eccentric arc rotor profile is formed by eccentric design to improve the shape coefficient and volume utilization ratio. Secondly，the shape coefficient and volume utilization rate are further improved by the design of convex top arc for sealing. Thirdly，The shape coefficient and volume utilization ratio of the two blades of the three circular rotors are calculated as examples. All results indicated that the percentage increase of shape coefficient and volume utilization rate with eccentric circular are 1.42% and 2.24% higher than common arc rotors. And the half angle of convex head is from 1° to 8°，the percentage increase of shape coefficient and volume utilization rate of two blades arc rotors with convex head is from 1.95% to 7.26% and from 3.58% to 11.84% higher than common arc rotors，increase effect was obvious. And the convex head structure is simple and easy to process. It is concluded that a new enhancement design is provided for other profile geometry in roots pump.